Investigating inequality trends in Africa: ACEIR research and the WIID - Martin Wittenberg; Murray V. Leibbrandt (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Work done by the African Centre of Excellence for Inequality Research (ACEIR) has documented the many-faceted nature of inequality in Ghana, Kenya, and South Africa. Conventionally measured inequality ranges from moderate (in Ghana) to extremely high (in South Africa). Trying to tell one coherent story about African inequality, however, is difficult. The construction of comparable measures across countries and across time runs into the problem that data quality varies across instruments. International databases of inequality, such as the World Income Inequality Database (WIID), sit on top of this fragile foundation. Institutions, like ACEIR, have focused on interrogating the reliability of inequality estimates in a few specific country contexts and attempted to harmonize the underlying information. As WIID provides very careful documentation detailing data that has been used and the methods applied in deriving their estimates of levels and trends, it has been possible to compare these statistics with those produced by ACEIR in Ghana, Kenya, and South Africa. The underlying country-specific income and expenditure data are subject to quality changes which get smoothed over by the WIID estimates. This brings uncertainty into the WIID estimates that is not reflected in each point estimate. This uncertainty depends on the specific local surveys that are selected as the basis for the WIID estimates.
Keywords: C8; D31; 330; inequality measurement; Ghana; Kenya; South Africa; WIID